Habaib in Batavia in the 17th Century: A Study on the Roles of Habaib in the Process of Islamization and Islamic Preaching - Permana, Agus; Mawardi, Mawardi (TAWARIKH, 2017)
ABSTRACT: The development of Islam in Batavia (Jakarta now) is not only the struggle of scholarsâ Haji (one who has made the pilgrimage to Mecca) of Batavia, but also the merit of scholars of Jakarta coming from Arab-Hadramaut. The study is aimed at identifying the Islamization process in Batavia and analysing the roles of âHabaibâ in the Islamization process in the 17thcentury. The method employed in the study was historical method by using four steps of main activities, i.e heuristic as a step to collect historical data; criticism as an activity to criticize the data; interpretation as a step to provide elucidation on data; and historiography as a phase of history writing. The result shows that the process of Islamization in Batavia was closely related to the beginning of Batavia conquering by Fatahillah or Fadhillah Khan in 1527 AD (Anno Domini). However, some writings have early criticized the theory stating that the growth of Islamization process in Batavia would be more appropriate if linked to Muslim sholars, such as Syekh Quro (Karawang), Datuk Ibrahim (Condet), Datu Biru (Jatinegara), Dato Tonggara (Cililitan), Mak Datu Tanjung Kait (Tangerang), and Kumpi Datu (Depok). In addition, in the 17thcentury, the growth of Islamization process in Batavia increased since âHabaibâ from Arab-Hadramaut had come to Batavia. Their existences were proved by the historical facts found in Batavia, they are site of Kampung Bandan and site of Kampung Luar Batang.KEY WORDS: Habaib of Batavia; Process of Islamization; History of Muslims; Speech; Historical Sites.Â Â About the Authors: Agus Permana and Mawardi are the Lecturers at the Faculty of Adab and Humanities UIN SGD (State Islamic University, Sunan Gunung Djati) Bandung, Jalan A.H. Nasution No.105 Cipadung, Bandung 40614, West Java, Indonesia. For academic interests, the authors are able to be contacted via e-mails at: aguspermana978@gmail.com and mawardiyahya@gmail.comRecommended Citation: Permana, Agus & Mawardi. (2017). âHabaib in Batavia in the 17th Century: A Study on the Roles of Habaib in the Process of Islamization and Islamic Preachingâ in TAWARIKH: International Journal for Historical Studies, Vol.9(1), October, pp.23-32. Bandung, Indonesia: Minda Masagi Press and UIN SGD Bandung, ISSN 2085-0980.Article Timeline: Accepted (August 17, 2017); Revised (September 19, 2017); and Published (October 28, 2017).